Methyl CpG binding protein 2 promotes colorectal cancer metastasis by regulating N6‐methyladenosine methylation through methyltransferase‐like 14. Issue 8 (29th June 2021) - Wang, Shuo; Gan, Meifu; Chen, Chaoyi; Zhang, Yi; Kong, Jianlu; Zhang, Honghe; Lai, Maode
Abstract: RNA N 6 ‐methyladenosine (m 6 A) is an emerging regulatory mechanism for tumor progression in several types of cancer. However, the underlying regulation mechanisms of m 6 A methylation in colorectal cancer (CRC) remain unknown. Although the oncogenic function of methyl CpG binding protein 2 (MeCP2) has been reported, it is still unclear whether MeCP2 could alter RNA m 6 A methylation state. Here, we systematically identified MeCP2 as a prometastasis gene to regulate m 6 A methylation in CRC. Interestingly, MeCP2 could bind to methyltransferase‐like 14 (METTL14) to coregulate tumor suppressor Kruppel‐like factor 4 (KLF4) expression through changing m 6 A methylation modification. Furthermore, insulin‐like growth factor 2 mRNA‐binding protein 2 recognized the unique modified m 6 A methylation sites to enhance KLF4 mRNA stability. Taken together, these findings highlight the novel function of MeCP2 for regulating m 6 A methylation and reveal the underlying molecular mechanism for the interaction between MeCP2 and METTL14, which offers a better understanding of CRC progression and metastasis. Abstract : MeCP2 as a prometastasis gene and METTL14 as an antimetastasis gene in colorectal cancer. MeCP2 affects N 6 ‐methyladenosine (m 6 A) methylation through physically interacting with METTL14 . MeCP2 and METTL14 jointly regulate the target gene KLF4 through m 6 A methylation sites.